TRANSLATION STRATEGY IN TOBA DREAM MOVIE SUBTITLE - Manullang, Elisa Betty; Marpaung, Gabe Hartina (Jurnal Darma Agung; Vol 28 No 2 (2020): AGUSTUS 2020, 2020)
The article deals with the translation strategies used in Toba Dream Movie. The objectives of this study were to find out types and most dominant type of translation strategies used in the subtitles of Toba Dream movie. The study was conducting by using descriptive qualitative method. The data of the study were words, ph ra ses, and clauses in the subtitle of  Toba   Dream movie, there  were 425 dialogues in the movie. The data analysis were taken by listing and tabulating the data. The data were analyzed based on the theory that proposed by Henrik Gottlieb. The findings ind u cted that there   were ten types of translation strategies used in the movie, they were t here were (319 times)used transfer strategy,  (37 times) used paraphrase, (27 times) used dislocation, (20 times)used resignation, (10times) used expansion, (5 times)used decimation, (4 times) utterances which used conde s ation, (1time) used imitation, (1time) used transcription and (1time) used deletion. The dominant strategy used in the subtitles of Toba Dream movie was tra n sfer strategy where the tra n slator  translated the dialogues completely and correctly.